A layered porous composite membrane and method of manufacture
Patent Information
- Application Number
- CN202611450085.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-18
- Publication Date
- 2026-10-23
AI Technical Summary
然而,在充放电循环过程中产生的锌枝晶或铁枝晶现象,容易刺穿传统的无纺布型电池隔膜,造成电池短路
[0015]本申请实施例提供的技术方案至少带来以下有益效果:本申请利用材料自身的热熔属性进行无粘合剂复合,避免了外部粘合剂引入带来的杂质,有效防止了微多孔薄膜的微观孔隙被堵死,保持了孔径分布的均匀性。经过射频等离子体改性后,微多孔薄膜层的水接触角从95°下降至45°,表面能从30mN/m提升至52mN/m。该复合膜应用于反渗透膜支撑材时,能够直接替代传统聚砜层,从根源上免去了大量有机溶剂的使用,降低了环保压力和能耗成本。此外,多孔薄膜与无纺布的交叉叠合结构,使复合膜的拉伸强度达到120MPa、抗穿刺强度达到3.5N,相较于裸膜提升3倍以上。更能在二次电池应用中构建起坚固的多孔物理阻挡网络,在500次充放电循环后容量保持率仍达92%,未发生短路现象,有效抑制锌枝晶和铁枝晶的生长,提高了电池运行的安全性。
Smart Images

Figure CN122956823A_ABST
Abstract
Description
Technical Field
[0001] This application relates to the field of layered composite membrane technology, and more specifically, to a layered porous composite membrane and its manufacturing method. Background Technology
[0002] A conventional reverse osmosis membrane structure typically consists of a nonwoven fabric support, a polysulfone layer, and a polymer layer. In the manufacturing process, polysulfone is first dissolved in an organic solvent to prepare a casting solution, which is then coated onto one side of the nonwoven fabric support using methods such as slot coating. A phase inversion process forms the bottom layer, which is then followed by interfacial polymerization to form the reverse osmosis membrane. During this process, the preparation of the polysulfone layer consumes a large amount of harmful organic solvents, and the phase inversion process requires washing with large amounts of deionized water, resulting in significant organic solvent dissolution in the wastewater. Improper treatment of this wastewater can cause serious environmental pollution. Furthermore, the high-temperature water bath required to maintain the phase inversion process leads to substantial energy consumption, making the preparation cost of the polysulfone layer a significant proportion of the overall cost of the reverse osmosis membrane.
[0003] With the development of the energy storage industry, aqueous secondary batteries with high safety have broad application prospects. However, zinc or iron dendrites generated during charge-discharge cycles can easily puncture traditional non-woven battery separators, causing short circuits. While ordinary anti-dendritic porous membranes can physically block dendrites, their low mechanical strength, difficulty in equipment control, and tendency to wrinkle during operation make them unsuitable for direct use as independent separators. If conventional chemical adhesives are used to bond the porous membrane and non-woven fabric, the micropores of the membrane are easily blocked by impurities and adhesives, severely affecting the ion flux and distribution uniformity of the separator. Therefore, there is an urgent need in this field for a composite membrane material with high strength, high porosity maintenance, and environmental friendliness. Summary of the Invention
[0004] This application provides a layered porous composite membrane and its manufacturing method. By selecting a specific structure and using a binder-free hot-pressing composite process, pore blockage is avoided, significantly reducing environmental and energy costs in the production process. After radio frequency plasma modification treatment, the water contact angle of the polypropylene microporous film layer decreases from 95° before modification to 45°, and the surface energy increases from 30 mN / m to 52 mN / m, significantly enhancing the interfacial affinity with the sheath semi-molten body.
[0005] This application provides a layered porous composite membrane, comprising: a microporous film layer treated with high-energy modification; a wet-laid nonwoven fabric layer, alternately stacked with the microporous film layer; the wet-laid nonwoven fabric layer comprising core-sheath type fibers; the melting point of the sheath layer of the core-sheath type fibers is configured to be lower than the melting point of its core layer and lower than the melting point of the microporous film layer; the microporous film layer and the wet-laid nonwoven fabric layer are bonded together by adhesive-free lamination; the microporous film layer is made of polypropylene material, with a porosity configured to be 35% to 65% and a single-layer thickness configured to be 3μm to 100μm; the single-layer basis weight of the wet-laid nonwoven fabric layer is configured to be 5g / m³. 2 Up to 60g / m 2 Within a temperature range of 110°C to 125°C, the melt index (MFI) of the sheath is configured to be between 10 g / 10 min and 50 g / 10 min, indicating a semi-molten state.
[0006] Furthermore, the microporous film layer is made of polypropylene homopolymer or copolymer material; the maximum pore size of the microporous film layer is configured to be less than or equal to 1 μm, and the average pore size of the microporous film layer is configured to be less than or equal to 0.15 μm.
[0007] Further, the layered porous composite membrane includes a two-layer structure, a three-layer structure, a four-layer structure, or a five-layer structure; wherein, the two-layer structure is a combination of a microporous film layer and a wet-laid nonwoven fabric layer; the three-layer structure has a microporous film layer as the middle layer and wet-laid nonwoven fabric layers on both sides, or a wet-laid nonwoven fabric layer as the middle layer and microporous film layers on both sides; the four-layer structure has the microporous film layer, the wet-laid nonwoven fabric layer, the microporous film layer, and the wet-laid nonwoven fabric layer arranged alternately in sequence; the five-layer structure has the microporous film layer and the wet-laid nonwoven fabric layer arranged alternately in sequence, and the two outermost sides are both wet-laid nonwoven fabric layers; the high-energy modification treatment is configured as a plasma modification treatment performed in a vacuum environment containing a specific working gas composed of at least one of oxygen, nitrogen, and argon.
[0008] Furthermore, the core-sheath type fiber includes an inner core layer and a sheath layer covering the outer side of the core layer; the core-sheath type fiber is configured as one of polypropylene and polyethylene composite fiber, polyethylene terephthalate and polyethylene composite fiber, or polyethylene terephthalate and copolymer polyethylene terephthalate composite fiber.
[0009] Further, the core-sheath fiber includes a core layer and a sheath layer that completely covers the core layer; the melting point of the sheath layer is configured to be lower than the melting point of the core layer, and the melting point of the sheath layer is configured to be lower than the melting point of the polypropylene substrate in the microporous film layer, so that the sheath layer can be heated to a semi-molten state in the temperature range of 110°C to 125°C, with its melt flow index (MFI) in the range of 10 g / 10 min to 50 g / 10 min, and the core layer and the microporous film layer do not reach their melting points and remain solid; the cross-section of the core-sheath fiber in the wet-laid nonwoven fabric layer is circular or elliptical, the fiber length is configured to be in the range of 3 mm to 12 mm, and the fiber diameter is configured to be in the range of 2 μm to 20 μm; adjacent core-sheath fibers in the wet-laid nonwoven fabric layer crosslink at the intersection through the melting of the sheath layer to form an independent porous mesh support skeleton, and the porous mesh support skeleton is directly bonded to the surface of the microporous film layer after high-energy modification treatment.
[0010] This application also provides a method for manufacturing a layered porous composite membrane, which is used to manufacture the above-mentioned layered porous composite membrane. The manufacturing method includes: performing a high-energy modification treatment on the surface of the microporous film layer; alternately aligning and stacking the high-energy modified microporous film layer and the wet nonwoven fabric layer to form a multilayer composite substrate; controlling the roller surface temperature of the hot pressing device to be within the range of 110°C to 125°C, and controlling the hot pressing bonding speed to be within the range of 5 m / min to 20 m / min; feeding the multilayer composite substrate into the hot pressing device to perform an adhesive-free hot pressing bonding process, and outputting the layered porous composite membrane.
[0011] Furthermore, the high-energy modification treatment employs plasma modification treatment; the specific operational configuration for performing high-energy modification treatment on the surface of the microporous film layer includes placing the microporous film layer in a working gas atmosphere composed of at least one of oxygen, nitrogen, and argon, and bombarding the surface of the microporous film layer with plasma at radio frequency discharge power.
[0012] Further, the hot pressing device includes a preheating roller, a main hot pressing bonding roller, and a cooling and shaping roller; the process parameters of the hot pressing device are configured to: make the surface temperature of the preheating roller reach the softening point of the sheath layer of the core-sheath fiber; strictly limit the roller surface temperature of the main hot pressing bonding roller to the range of 110°C to 125°C, and control the hot pressing bonding speed to the range of 5 m / min to 20 m / min, so that the sheath layer of the core-sheath fiber is in a semi-molten state, and its melt flow index (MFI) is in the range of 10 g / 10 min to 50 g / 10 min; after being pressed by the main hot pressing bonding roller, the multilayer composite substrate is directly conveyed to the cooling and shaping roller, and the surface temperature of the cooling and shaping roller is configured to be in the range of 15°C to 30°C, so as to cool down the film material after hot pressing and shaping, and solidify the physical bonding state between the sheath layer of the core-sheath fiber and the surface of the microporous film layer.
[0013] This application also provides a reverse osmosis membrane support material, including the above-mentioned layered porous composite membrane.
[0014] This application also provides a battery separator, including the above-mentioned layered porous composite membrane.
[0015] The technical solution provided in this application provides at least the following beneficial effects: This application utilizes the inherent thermal fusion properties of the material for adhesive-free composite bonding, avoiding impurities introduced by external adhesives, effectively preventing the micropores of the microporous membrane from being blocked, and maintaining the uniformity of pore size distribution. After radio frequency plasma modification, the water contact angle of the microporous membrane layer decreases from 95° to 45°, and the surface energy increases from 30 mN / m to 52 mN / m. When this composite membrane is used as a reverse osmosis membrane support material, it can directly replace the traditional polysulfone layer, fundamentally eliminating the use of large amounts of organic solvents, reducing environmental pressure and energy consumption costs. Furthermore, the cross-over structure of the porous membrane and nonwoven fabric enables the composite membrane to achieve a tensile strength of 120 MPa and a puncture resistance of 3.5 N, more than three times higher than that of the bare membrane. It can also construct a robust porous physical barrier network in secondary battery applications, maintaining a capacity retention rate of 92% after 500 charge-discharge cycles without short circuits, effectively inhibiting the growth of zinc dendrites and iron dendrites, and improving the safety of battery operation. Attached Figure Description
[0016] Figure 1 This is a partial cross-sectional view of a layered porous composite membrane provided in an embodiment of the present invention.
[0017] Figure 2 This is a flowchart of a method for manufacturing a layered porous composite membrane provided in an embodiment of the present invention.
[0018] Figure 3This is a local microscopic morphology SEM image of the microporous thin film layer provided in the embodiment of the present invention.
[0019] Figure 4 This is a local microstructure SEM image of the microporous thin film layer provided in the embodiment of the present invention from another perspective.
[0020] Explanation of reference numerals in the attached figures:
[0021] In the figure: 101-microporous film layer, 102-wet nonwoven fabric layer, 301-microporous structure, 302-crack morphology, 1021-core-sheath fiber, 1022-core layer, 1023-sheath layer. Detailed Implementation
[0022] The technical solutions of the embodiments of this application will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of this application, and not all embodiments. Based on the embodiments of this application, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of this application.
[0023] In the field of microporous thin film composites, how to improve the strength of the substrate without sacrificing the porosity and permeation flux of the membrane itself has always been a challenge in process design. Traditional adhesive-containing composite processes inevitably lead to micropore blockage, resulting in reduced permeability of the final product. To address this, this application proposes a composite membrane structure and its manufacturing method that rely on the thermodynamic phase change bonding characteristics of the substrate interface.
[0024] According to one aspect of this application, a layered porous composite membrane is provided. Figure 1 This is a partial cross-sectional view of a layered porous composite membrane provided in an embodiment of the present invention. Figure 1 As shown, this layered porous composite membrane is composed of two different core substrates, configured as a microporous film layer 101 and a wet-laid nonwoven fabric layer 102. In terms of overall structural arrangement, the microporous film layer 101 and the wet-laid nonwoven fabric layer 102 are alternately stacked in the vertical direction. Furthermore, the introduction of chemical adhesives between the microporous film layer 101 and the wet-laid nonwoven fabric layer 102 is completely eliminated, and an adhesive-free lamination composite method is used to form an integrated structure.
[0025] For the first core substrate, the microporous thin film layer 101 must undergo high-energy modification treatment before entering the composite process. This treatment introduces polar groups on the surface of the microporous thin film layer 101, enhancing the affinity and physical bonding force between it and other materials. After radio frequency plasma modification, the water contact angle of the microporous thin film layer 101 decreases from 95° to 45°, and the surface energy increases from 30 mN / m to 52 mN / m. The single-layer thickness of the microporous thin film layer 101 is configured in the range of 3 μm to 100 μm, and its overall macroscopic porosity is configured in the range of 35% to 65%. In terms of pore size control, the maximum pore size of the microporous thin film layer 101 is strictly limited to less than or equal to 1 μm, and its average pore size is configured to be less than 0.15 μm. This submicron-level dense porous structure not only ensures sufficient flux but also effectively blocks macromolecules or metal dendrites. Furthermore, the microporous film layer 101 is made of polypropylene homopolymer or copolymer material; in some alternative embodiments, a microporous film made of polyester may also be used.
[0026] For the second core substrate, the wet-laid nonwoven fabric layer 102 is manufactured using a wet-laid papermaking process. To facilitate the subsequent adhesive-free hot-pressing lamination process, the wet-laid nonwoven fabric layer 102, as the second core structural layer, uses core-sheath type fibers 1021. In terms of macroscopic areal density, the single-layer basis weight of the wet-laid nonwoven fabric layer 102 is configured as 5 g / m². 2 Up to 60g / m 2 This lower basis weight design minimizes the thickness contribution while providing the necessary tensile strength. In terms of microstructure, the fibers used in the wet-laid nonwoven layer 102 have a fiber diameter configuration of 2μm to 20μm and a fiber length configuration of 3mm to 12mm. All fibers primarily exhibit a straight fiber morphology with a high degree of orientation.
[0027] like Figure 1 As shown, the core-sheath fiber 1021 exhibits a bicomponent distribution in its radial cross-section, comprising a core layer 1022 at the core support position and a sheath layer 1023 completely covering the core layer 1022. In this embodiment, the core-sheath fiber 1021 is configured as one of polypropylene and polyethylene composite fibers, polyethylene terephthalate and polyethylene composite fibers, or polyethylene terephthalate and copolymer polyethylene terephthalate composite fibers. Furthermore, the wet-laid nonwoven layer 102 can also be composed of the aforementioned core-sheath fiber 1021 mixed with conventional polypropylene single-component fibers or polyethylene terephthalate single-component fibers.
[0028] This core-sheath structure is characterized by a stepwise difference in thermodynamic properties. The melting point of the sheath layer 1023 is configured to be significantly lower than that of the core layer 1022; more importantly, the melting point of the sheath layer 1023 is also configured to be lower than that of the polypropylene substrate in the microporous film layer 101. When the above components are hot-pressed together, within the process temperature range of 110°C to 125°C, the sheath layer 1023 reaches a semi-molten state with a melt index (MFI) of 10 g / 10 min to 50 g / 10 min, while the core layer 1022 and the microporous film layer 101 retain their solid skeletal support capabilities. Thus, adjacent core-sheath type fibers 1021 in the wet-laid nonwoven layer 102 form a cross-linked network at their physical intersections through the melt of the sheath layer 1023. After cooling and solidification, these cross-linked points form an interconnected and independent macroporous network support skeleton within the wet-laid nonwoven layer 102. Simultaneously, the semi-molten sheath 1023 directly adheres and physically bonds to the high-surface-energy surface of the microporous film layer 101 after high-energy modification, achieving a strong interlayer composite. Through the synergistic effect of this specific porous mesh framework and the modified surface, the tensile strength of the film during processing can be significantly improved, effectively preventing wrinkling.
[0029] In the overall composite structure design, the layered porous composite membrane of this application can be configured as a two-layer, three-layer, four-layer, or even five-layer structure according to different application scenarios. In a two-layer structure, it includes a microporous film layer 101 and a wet-laid nonwoven fabric layer 102. If a three-layer structure is used, it is configured such that the middle layer is a microporous film layer 101 and the two sides are wet-laid nonwoven fabric layers 102, or the middle layer is a wet-laid nonwoven fabric layer 102 and the two sides are microporous film layers 101. Based on this, a four-layer structure is configured with alternating layers of microporous film layer 101, wet-laid nonwoven fabric layer 102, microporous film layer 101, and wet-laid nonwoven fabric layer 102. The arrangement logic of a five-layer structure follows the same pattern, always maintaining the alternation of two media, for example, a five-layer alternating structure where both outermost ends are wet-laid nonwoven fabric layers 102. The single microporous film layer 101 described above can be composed of a single extremely thin microporous film, or it can be composed of an assembly of two or more microporous films first stacked and composited without adhesive; similarly, the single wet nonwoven fabric layer 102 described above can also be composed of two or more single-layer nonwoven fabrics pre-stacked and composited.
[0030] Figure 3 This is a local microscopic morphology SEM image of the microporous thin film layer provided in the embodiment of the present invention. Figure 4 This is a SEM image of the local microstructure of the microporous thin film layer provided in an embodiment of the present invention, from another perspective. For example... Figure 3 and Figure 4As shown, using a scanning electron microscope, the surface features of the microporous film were observed under test conditions with a magnification of 1000x, an observation scale of 10μm, and an accelerating voltage of 10.0kV. It can be clearly observed that the film surface is covered with a dense microporous structure 301, and fine crack morphology 302 accompanies adjacent pores. This microstructure verifies the film material's performance in maintaining high porosity and pore size consistency.
[0031] According to another aspect of this application, a method for manufacturing a layered porous composite membrane is provided. Figure 2 This is a flowchart of the manufacturing method provided in an embodiment of the present invention. For example... Figure 2 As shown, this method includes a series of strictly controlled pretreatment, lamination, and thermodynamic phase change curing processes, which are described in detail below.
[0032] S201: Before formally entering the composite stage, a pre-processing step for preparing wet-laid nonwoven fabric is performed. This step utilizes wet-laid papermaking technology, using water as the dispersion medium, to disperse and prepare a pulp with a mass concentration of 0.1% to 0.2% for core-sheath type fibers 1021, with fiber lengths ranging from 3mm to 12mm and fiber diameters ranging from 2μm to 20μm. A single-wire inclined wire paper machine with a central pulp distributor is used to perform wire forming operations on the pulp. During this process, the system controller monitors the forming parameters, controlling the pulp wire concentration within the range of 0.005% to 0.05%, and controlling the fiber arrangement direction of the formed output, maintaining the longitudinal to transverse fiber ratio between 1:1 and 1.5:1, thereby giving the nonwoven fabric anisotropic strength characteristics. After the sizing process is completed, the wet nonwoven fabric fiber material is independently transported to a through-type drying tunnel or through-type drying cage for drying and shaping. The hot air temperature in this drying environment is precisely controlled within the range of 135℃ to 165℃, ultimately producing a wet nonwoven fabric layer 102 that meets the weight specifications. This pre-drying process is applied independently to the wet nonwoven fabric layer; the microporous film layer does not enter the drying tunnel, thus avoiding thermal damage.
[0033] The surface of the prepared microporous film layer 101 is subjected to high-energy modification treatment. This treatment is used to activate the inert chemical bonds on the film surface. In this embodiment, plasma modification treatment is used. Specifically, the microporous film layer 101 is placed in a dedicated vacuum plasma treatment chamber, and a working gas is injected. The gas atmosphere is configured to consist of at least one of oxygen, nitrogen, and argon. At a radio frequency discharge power sufficient to excite the plasma, the microporous film layer 101 is bombarded with plasma at a moving speed of 2 m / min to 25 m / min, and the treatment time for a single surface is controlled between 5 s and 30 s. Testing showed that the water contact angle of the modified microporous film layer 101 decreased from 95° to 45°, and the surface energy increased from 30 mN / m to 52 mN / m.
[0034] S202: The microporous film layer 101, which has undergone high-energy modification and possesses high surface activity, and the prepared wet-laid nonwoven fabric layer 102 are guided to the composite station. According to the pre-configured structural pattern, the feeding speed and guidance of the two are adjusted by a tension control mechanism to ensure that they are precisely aligned alternately and stacked to form an uncured multilayer composite substrate.
[0035] S203: Configure and initialize the process parameters of the multi-roller hot press device. The system controller acquires the melting point data of the sheath layer 1023 and the film substrate, and issues temperature control commands based on this. The core parameter determining the success rate of lamination, the roller surface temperature, is strictly limited to the range of 110℃ to 125℃, and the drive source of the conveyor belt and rollers is controlled simultaneously to keep the hot pressing bonding speed between 5 m / min and 20 m / min. The temperature range is set based on the following: the melting point of the sheath layer 1023 is approximately 120-130℃, and its melt index (MFI) reaches 10 g / 10 min to 50 g / 10 min within the range of 110℃ to 125℃, indicating a semi-molten state; while the melting point of the polypropylene microporous film layer 101 is approximately 165℃, and it remains solid at 125℃.
[0036] S204: The multilayer laminated substrate is fed into the hot press device to perform a multi-stage adhesive-free hot press lamination process. The hot press device is sequentially equipped with a preheating roller, a main hot press bonding roller, and a cooling and shaping roller along the material flow direction. The multilayer laminated substrate first contacts the preheating roller, whose surface temperature is configured to allow the outer sheath layer 1023 of the core-sheath fiber 1021 to reach its softening point. The substrate enters the rolling gap of the main hot press bonding roller, where appropriate mechanical compressive stress is superimposed at a controlled temperature of 110°C to 125°C. At this point, the sheath layer 1023 transforms into a semi-molten state, with a melt flow index (MFI) reaching 10 g / 10 min to 50 g / 10 min, forming a flowing bonding interface and enveloping the surrounding microporous film layer surface; while the microporous film layer body and the core layer 1022, having not reached their respective melting points, retain their original physical mesh and support structure intact. The system controller adjusts the gap between the main pressing rollers to stabilize the overall thickness of the final layered porous composite membrane between 50μm and 450μm. The high-temperature membrane material, immediately after leaving the main hot pressing rollers, is conveyed to the cooling and setting rollers. The cooling and setting rollers maintain the surface temperature between 15℃ and 30℃ through internal refrigerant circulation. The substrate is pressed against the surface of the cooling rollers for cooling treatment, causing the semi-molten sheath layer 1023 to crystallize and solidify, permanently anchoring the three-dimensional network nodes within the wet-laid nonwoven fabric and its physical bonding with the microporous membrane interface. Testing revealed that the resulting composite membrane has a tensile strength of 120MPa and a puncture resistance of 3.5N.
[0037] S205: Based on the final application functional requirements of the layered porous composite membrane, the composite membrane material from the hot-pressing line is sent to the post-processing module. The post-processing module is configured to perform one or more functional modification treatments, such as corona treatment, plasma treatment, sulfonation, grafting, coating, or impregnation with active substance solutions, to meet special application requirements such as hydrophilic enhancement or ion-selective permeation. Through continuously controlled hot-pressing and phase change anchoring steps, large-area, high-peel-strength industrial composites of heterogeneous porous membrane materials can be achieved while avoiding foreign matter clogging the micropores.
[0038] To further verify the technical synergy and effectiveness of this application in material composition selection and thermodynamic process parameter setting, the following four sets of specific parameter configuration implementation test examples and one set of comparative examples are provided by extracting and summarizing real trial production data from the research and development process of this application.
[0039] Example 1 uses 100% by mass polypropylene and polyethylene composite core-sheath type fibers with a diameter of 10 μm and a length of 3 mm to prepare fibers with a basis weight of 40 g / m². 2 A single layer of wet-laid nonwoven fabric was used. A 20 μm thick polypropylene microporous film layer with a porosity of 45% was selected as the substrate. In the plasma modification stage, the environment was set to 100% pure oxygen atmosphere, the radio frequency discharge power was set to 2000W, the processing speed was 8 m / min, and the processing time lasted for 15 s. After modification, the contact angle decreased from 95° to 45°, and the surface energy increased from 30 mN / m to 52 mN / m. The composite structure consisted of two layers: a film and a nonwoven fabric. A 5-roll calender was used, with the temperature of the hot-pressing rollers precisely controlled at 120℃, and the bonding speed set to 13 m / min. After pressing, a composite film with a thickness of approximately 200 μm was obtained, and its surface was subjected to corona hydrophilic modification. Testing showed that the porosity remained at 44% after lamination, the tensile strength was 115 MPa, and the puncture resistance was 3.4 N.
[0040] Example 2 uses a wet-laid nonwoven fabric made of 50% by mass of polypropylene and polyethylene composite core-sheath fibers with a diameter of 12 μm and a length of 5 mm, 20% by mass of polypropylene and polyethylene composite core-sheath fibers with a diameter of 5 μm, and 30% by mass of pure polypropylene straight fibers with a diameter of 8 μm and a length of 3 mm. A microporous film layer with a thickness of 16 μm and a porosity of 45% is selected. The plasma treatment configuration is: 100% oxygen content, power 2200 W, speed 10 m / min, treatment for 13 s. In terms of composite arrangement, three modified films are first hot-pressed together to form a single thickened film material, and then this thickened film material is laminated with the above single-layer nonwoven fabric under the conditions of roller surface temperature 135°C and speed 13 m / min. The resulting material is then impregnated with active material for use in the preparation of battery separators.
[0041] Example 3 uses a core-sheath type fiber composed of polypropylene and polyethylene composites with a mass fraction of 50% (12 μm diameter, 5 mm length) and 50% (5 μm diameter, 3 mm length) to prepare an extremely thin slurry with a web-forming concentration of 0.015%, resulting in a relatively thin 7 g / m² fiber. 2 Non-woven fabric. A 70μm thick, 40% porosity polypropylene microporous membrane was selected. Plasma parameters were increased to 3000W power and 12m / min speed. The structural arrangement was as follows: a three-layer structure with a polypropylene microporous membrane layer in the center, and an extremely thin non-woven fabric layer covering the upper and lower surfaces. The hot-pressing temperature was adjusted to 137℃ and the speed to 15m / min.
[0042] Example 4 uses the same mixed fiber formulation as Example 2 to prepare a product with a basis weight of 20 g / m². 2 The nonwoven fabric used is a 16μm polypropylene microporous film layer with a porosity of 42%. The plasma treatment parameters were 2000W and 12 meters / minute. The structural arrangement is a complex four-layer alternating structure: film, nonwoven fabric, film, nonwoven fabric stacked sequentially. The hot-pressing conditions were 125℃ and 12 meters / minute. Furthermore, to effectively verify and support the feasibility of manufacturing thinner films, multilayer lamination verification was conducted using microporous film substrates with thicknesses ranging from 3μm to 5μm, combined with wet-laid nonwoven fabric of corresponding weight. The results confirmed that even at the extreme thickness, controlling the hot-pressing conditions at around 120℃ still resulted in the formation of a stable porous cross-linked framework, meeting the aforementioned physical strength requirements. Testing showed that the composite film of this embodiment, when applied to an aqueous zinc-ion battery, maintained a capacity retention of 92% after 500 charge-discharge cycles without experiencing short circuits.
[0043] As a comparative example for reverse verification, all front-end materials and processes in Example 1 were completely replicated. The only variable controlled was that the surface temperature of the main hot-press bonding roller was increased to 140°C during the hot-press bonding process.
[0044] The samples produced in Examples 1 to 4, along with comparative samples that deviated from the temperature control range, were simultaneously sent to the laboratory for standard performance testing. Key mechanical and microfluidic data were obtained using a bubble-pressure filter membrane pore size analyzer and a fabric stretching machine. Specific lateral performance comparison mapping data are summarized in the table below. It should be noted that in each example and comparative example, the thickness, material, and porosity of the pre-composite microporous membrane can be adjusted according to specific application requirements. The specific parameters of the pre-composite microporous membrane used in each example are detailed in the corresponding example.
[0045] Table 1. Lateral Performance Test Data for Each Embodiment and Comparative Example
[0046]
[0047] Note: Table 1 lists the initial test data of the composite pre-microporous polypropylene membranes used in each embodiment and comparative example. The specific thickness and porosity of the composite pre-microporous membranes used in each embodiment have been detailed in the corresponding embodiment. Table 1 also includes key mechanical and electrochemical performance data such as tensile strength (MPa), puncture resistance (N), tensile modulus (MPa), and capacity retention rate after 500 cycles (%). Through comparative analysis of the above matrix test data, the technical conclusion can be drawn: Tests 1 to 4 in Table 1 correspond to the samples of Examples 1 to 4 above. After introducing the wet nonwoven fabric skeleton, the tensile strength is increased by several orders of magnitude compared with the bare membrane. Moreover, thanks to the core-sheath melting point difference mechanism and strict temperature upper limit protection, the pore size distribution, porosity, and air flux index symbolizing permeability after composite are all consistent, proving that its micro-filtration channels are not damaged. In contrast, the comparative test specimens pressed at a high temperature of 140℃, while achieving high peel and tensile strength, showed a significant decrease in flux to 0.0318 and porosity to 10.3%. The physical failure mechanism lies in the fact that when the roller surface temperature reaches 140℃, it is close to the upper limit of the heat distortion temperature of the polypropylene microporous film layer, leading to creep collapse and pore wall adhesion in the microporous structure, resulting in irreversible large-area closure of the pore size. Simultaneously, excessive external heat conduction causes excessive liquefaction and overflow of the core sheath fiber layer inside the nonwoven fabric layer, and even the supporting core layer structure undergoes yielding and rheological changes. This causes the original breathable three-dimensional mesh to be filled and solidified by the molten polymer, transforming into a dense semi-plastic film that blocks fluid passage. Experimental data show that defining the hot-pressing temperature within the range of 110℃ to 125℃ achieves composite reinforcement and porosity retention.
[0048] The layered porous composite membrane product prepared based on the above embodiments provides an application solution for reverse osmosis membrane support materials. In the water treatment equipment manufacturing industry, the main framework of the reverse osmosis membrane support material directly includes the layered porous composite membrane. In this application scenario, the modified microporous thin film layer 101 at the top of the composite membrane, with its optimized submicron-level dense surface morphology, completely replaces and supersedes the historical function of the polysulfone layer in terms of structural and mechanical support properties. This innovative application of dry thermophysical bonding instead of wet coating and crosslinking allows the preparation process of the support material to completely eliminate dependence on toxic organic solvents, preventing the harm of industrial wastewater from the source of pollution and meeting the green manufacturing standard of zero discharge. On the other hand, it eliminates the high-energy-consuming steps such as high-temperature pure water washing and drying required for phase transformation, reducing the overall mass production cost and process time of the bottom support component of the reverse osmosis membrane.
[0049] To address the electrochemical isolation requirements within new energy storage systems, a battery separator application solution is provided. This battery separator also employs a layered porous composite membrane as its core functional layer. Specifically, this separator is highly compatible with secondary battery architectures that emphasize high-safety cycling, such as aqueous zinc-ion batteries, zinc-silver batteries, and novel iron-nickel batteries. Under these operating conditions, this application fully leverages the dual-modal interception mechanism of the macroscopic strong support framework effect provided by the wet-laid nonwoven layer 102 within the composite membrane and the homogeneous fine-pore barrier constructed by the microporous film layer 101. During long-term high-current charge-discharge cycles, zinc or iron dendrites with sharp morphologies easily precipitate on the surface of the metal anode. This composite battery separator, with its robust mesh cross-linking characteristics and 3.5N puncture resistance of the microporous film layer, applies rigid barriers and disperses stress on the disordered growth of spiky dendrites at the microscopic physical level, preventing dendrites from penetrating the separator and reaching the cathode, thus physically suppressing the occurrence of internal short circuits. Real-world testing data shows that after 500 charge-discharge cycles in an aqueous zinc-ion battery, the membrane retained 92% of its capacity without experiencing short circuits. Furthermore, the use of an adhesive-free intrinsic bonding method avoids the introduction of impurities, ensuring excellent pore consistency in the membrane material. This allows the electrolyte to flow smoothly and evenly, resulting in improved conductivity and longer cycle life for the energy storage battery while maintaining puncture resistance.
[0050] This application successfully overcomes the technical bottleneck of micropore closure and physical structure collapse in adhesive-free composite scenarios by designing a layered architecture consisting of alternating high-energy modified microporous film layers and specific core-sheath type nonwoven fabrics, combined with a precisely temperature-controlled adhesive-free thermoforming process. This achieves tensile mechanical properties that are doubled compared to single-layer bare membranes. This composite membrane can serve as a reverse osmosis support material to replace polysulfone layers, promoting industrial greening, and also as a high-strength separator to suppress dendrite growth in secondary batteries, achieving the advantages of both economic and environmental benefits and wide-scale industrial applicability.
[0051] The above provides a detailed description of a layered porous composite membrane and its manufacturing method. Specific examples have been used to illustrate the principles and implementation methods of this application. The descriptions of the above embodiments are only for the purpose of helping to understand the method and core ideas of this application. At the same time, for those skilled in the art, there will be changes in the specific implementation methods and application scope based on the ideas of this application. The content of this specification should not be construed as a limitation of this application.
Claims
1. A layered porous composite membrane, characterized in that, include: A microporous film layer undergoing high-energy modification; a wet-laid nonwoven fabric layer, alternately stacked with the microporous film layer; the wet-laid nonwoven fabric layer comprises core-sheath type fibers; the melting point of the sheath layer of the core-sheath type fibers is configured to be lower than the melting point of its core layer and lower than the melting point of the microporous film layer; the microporous film layer and the wet-laid nonwoven fabric layer are bonded together by adhesive-free lamination; the porosity of the microporous film layer is configured to be 35% to 65%, and the single-layer thickness is configured to be 3μm to 100μm; the single-layer basis weight of the wet-laid nonwoven fabric layer is configured to be 5g / m³. 2 Up to 60g / m 2 Within a temperature range of 110°C to 125°C, the melt index (MFI) of the sheath is configured to be between 10 g / 10 min and 50 g / 10 min, indicating that it is in a semi-molten state.
2. The layered porous composite membrane as described in claim 1, characterized in that, The microporous film layer is made of polypropylene homopolymer or copolymer material; the maximum pore size of the microporous film layer is configured to be less than or equal to 1 μm, and the average pore size of the microporous film layer is configured to be less than or equal to 0.15 μm.
3. The layered porous composite membrane as described in claim 2, characterized in that, The layered porous composite membrane includes a two-layer structure, a three-layer structure, a four-layer structure, or a five-layer structure. The two-layer structure is a combination of a microporous film layer and a wet nonwoven fabric layer. The three-layer structure is either a middle layer consisting of the microporous film layer and two sides consisting of the wet-laid nonwoven fabric layer, or a middle layer consisting of the wet-laid nonwoven fabric layer and two sides consisting of the microporous film layer. The four-layer structure consists of the microporous film layer, the wet-laid nonwoven fabric layer, the microporous film layer, and the wet-laid nonwoven fabric layer arranged alternately in sequence; The five-layer structure consists of alternating layers of microporous film and wet-laid nonwoven fabric, with the outermost two sides being the same wet-laid nonwoven fabric layer. The high-energy modification process is configured as a plasma modification process performed in a vacuum environment containing a specific working gas consisting of at least one of oxygen, nitrogen, and argon.
4. The layered porous composite membrane as described in claim 1, characterized in that, The core-sheath type fiber includes an inner core layer and a sheath layer covering the outer side of the core layer; the material configuration of the core-sheath type fiber is one of polypropylene and polyethylene composite fiber, polyethylene terephthalate and polyethylene composite fiber, or polyethylene terephthalate and copolymer polyethylene terephthalate composite fiber.
5. The layered porous composite membrane as described in claim 4, characterized in that, The core-sheath fiber includes a core layer and a sheath layer that completely covers the core layer; the sheath layer is made of polyethylene; the core layer is made of polypropylene or polyethylene terephthalate; the melting point of the sheath layer is configured to be lower than that of the core layer, and the melting point of the sheath layer is configured to be lower than that of the polypropylene substrate in the microporous film layer, so that the sheath layer can be heated to a semi-molten state in the temperature range of 110°C to 125°C, and the core layer and the microporous film layer do not reach their melting points and remain solid; the cross-section of the core-sheath fiber in the wet-laid nonwoven fabric layer is circular or elliptical, the fiber length is configured to be in the range of 3mm to 12mm, and the fiber diameter is configured to be in the range of 2μm to 20μm; adjacent core-sheath fibers in the wet-laid nonwoven fabric layer cross-link at the intersection through the melting of the sheath layer to form an independent porous mesh support skeleton, and the porous mesh support skeleton is directly bonded to the surface of the microporous film layer after high-energy modification treatment.
6. A method for manufacturing a layered porous composite membrane, characterized in that, The method for manufacturing a layered porous composite membrane as described in any one of claims 1 to 5 comprises: The surface of the microporous film layer is subjected to high-energy modification treatment; The microporous film layer that has undergone high-energy modification treatment is alternately aligned and stacked with the wet nonwoven fabric layer to form a multilayer composite substrate; The roller surface temperature of the hot pressing device is controlled within the range of 110°C to 125°C, and the hot pressing bonding speed is controlled within the range of 5 m / min to 20 m / min, so that the sheath layer of the core-sheath type fiber reaches a semi-molten state with a melt index (MFI) of 10 g / 10 min to 50 g / 10 min. The multilayer composite substrate is fed into the hot press device to perform a binder-free hot press composite process. The roller surface temperature of the hot press device is controlled within the range of 110°C to 125°C, so that the melt flow index (MFI) of the sheath layer reaches 10g / 10min to 50g / 10min, and the layered porous composite membrane is output.
7. The method for manufacturing the layered porous composite membrane as described in claim 6, characterized in that, The high-energy modification treatment employs plasma modification treatment; the specific operation configuration for performing high-energy modification treatment on the surface of the microporous film layer includes placing the microporous film layer in a working gas atmosphere composed of at least one of oxygen, nitrogen and argon, and bombarding the surface of the microporous film layer with plasma at radio frequency discharge power.
8. The method for manufacturing the layered porous composite membrane as described in claim 7, characterized in that, The hot pressing device includes a preheating roller, a main hot pressing bonding roller, and a cooling and shaping roller. The process parameters of the hot pressing device are configured as follows: the surface temperature of the preheating roller reaches the softening point of the sheath layer contained in the core-sheath fiber; the roller surface temperature of the main hot pressing bonding roller is strictly limited to the range of 110°C to 125°C, and the hot pressing bonding speed is controlled to be within the range of 5 m / min to 20 m / min, so that the sheath layer of the core-sheath fiber is in a semi-molten state, with a melt flow index (MFI) between 10 g / 10 min and 50 g / 10 min; after being pressed by the main hot pressing bonding roller, the multilayer laminated substrate is directly conveyed to the cooling and shaping roller, with the surface temperature of the cooling and shaping roller configured to be within the range of 15°C to 30°C, to cool the film material after hot pressing and shaping, thus solidifying the physical bonding state between the sheath layer of the core-sheath fiber and the surface of the microporous film layer.
9. A reverse osmosis membrane support material, characterized in that, Includes the layered porous composite membrane according to any one of claims 1 to 5.
10. A battery separator, characterized in that, Includes the layered porous composite membrane according to any one of claims 1 to 5.